Statistical modeling of Si-based refractory compounds of bamboo leaf and alumina reinforced Al–Si–Mg alloy hybrid composites - Olanrewaju S. Adesina; Adeolu A. Adediran; Francis O. Edoziuno; Olufemi O. Sanyaolu; Babatunde A. Obadele (Scientific Reports, 2023)
Abstract Wear properties of Al–Mg–Si alloy matrix hybrid composites made with Si-based refractory compounds (SBRC) derived from bamboo leaf ash (BLA) as complimentary reinforcement with alumina have been studied. The experimental result indicate that optimum wear loss was obtained at higher sliding speed. The wear rate of the composites increased with an increase in BLA wt. %, with the composites having 4%SBRC from BLA + 6% alumina (B4) showing the least wear loss for the different sliding speeds and wear loads considered. With increasing BLA weight percent, the composites' wear mechanism was mostly abrasive wear. Numerical optimization results using central composite design (CCD) reveal that at a wear load of 587.014N, sliding speed of 310.053 rpm and B4 hybrid filler composition level respectively, minimum responses in wear rate (0.572mm2/min), specific wear rate (0.212cm2/g.cm3) and wear loss (0.120 g) would be obtained for the developed AA6063 based hybrid composite. Perturbation plots indicate that the sliding speed have more impact on wear loss, while wear load have significant impact on the wear rate and specific wear rate.